Accelerated onset of chronic wasting disease in elk (Cervus canadensis) vaccinated with a PrPSc-specific vaccine and housed in a prion contaminated environment. Issue 50 (29th November 2018) - Wood, Mary E.; Griebel, Philip; Huizenga, Matthew L.; Lockwood, Samuel; Hansen, Cole; Potter, Andrew; Cashman, Neil; Mapletoft, John W.; Napper, Scott
Highlights: Vaccination induced elevated YYR-specific antibody titers in all animals. Survival of vaccinated 132MM elk was significantly shorter than controls. Survival of vaccinated 132ML elk was not significantly different from controls. There was no significant correlation between antibody titers and survival time. Abstract: Chronic wasting disease (CWD) is a fatal prion disease affecting multiple cervid species. Effective management tools for this disease, particularly in free-ranging populations, are currently limited. We evaluated a novel CWD vaccine in elk ( Cervus canadensis ) naturally exposed to CWD through a prion-contaminated environment. The vaccine targets a YYR disease-specific epitope to induce antibody responses specific to the misfolded (PrP Sc ) conformation. Female elk calves (n = 41) were captured from western Wyoming and transported to the Thorne-Williams Wildlife Research Center where CWD has been documented since 1979. Elk were held in contaminated pens for 14 to 20 days before being alternately assigned to either a vaccine (n = 21) or control group (n = 20). Vaccinated animals initially received two vaccinations approximately 42 days apart and annual vaccinations thereafter. Vaccination induced elevated YYR-specific antibody titers in all animals. Elk were genotyped for the prion protein gene at codon 132, monitored for clinical signs of CWD through daily observation, for disease status through periodic biopsy of rrectoanal mucosa-associated lympoid tissue (RAMALT), and monitored for YYR-specific serum antibody titres. Mean survival of vaccinated elk with the 132MM genotype (n = 15) was significantly shorter (800 days) than unvaccinated elk (n = 13) of the same genotype (1062 days; p = 0.003). Mean days until positive RAMALT biopsy for 132MM vaccinated elk (6 7 8) were significantly shorter than unvaccinated 132MM elk (990; p = 0.012). There was, however, no significant difference in survival between vaccinated (n = 4) and control (n = 5) elk with the 132ML genotype (p = 0.35) or in timing of positive RAMALT biopsies of 132ML elk (p = 0.66). There was no strong (p = 0.17) correlation between YYR-specific antibody titers and survival time. Determining the mechanism by which this vaccine accelerates onset of CWD will be important to direct further CWD vaccine research.